2021
DOI: 10.1007/s10869-021-09744-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions and General Distress for Essential and Nonessential Employees During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic and outbreak response represent a global crisis that has affected various aspects of people’s lives, including work. Speculation is rife about the impact of the crisis on employees. Countries and organizations worldwide have categorized some work as essential and, by extension, other work as nonessential. This study aims to investigate the impact of the pandemic by examining the relationship between work disruptions (at time 1) and general distress (at time 2) through various work stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Further research may heed the calls from various scholars to further examine the impact of this health pandemic on workers from different professions, organizations and with various occupational statuses. For instance, a recent study demonstrated that essential and non-essential workers may both experience mental health problems, but these may be triggered by different stressors (van Zoonen & ter Hoeven, 2021). Third, our sample was female dominated and further studies should address the gender differences.…”
Section: Limitations and Future Researchmentioning
confidence: 88%
See 3 more Smart Citations
“…Further research may heed the calls from various scholars to further examine the impact of this health pandemic on workers from different professions, organizations and with various occupational statuses. For instance, a recent study demonstrated that essential and non-essential workers may both experience mental health problems, but these may be triggered by different stressors (van Zoonen & ter Hoeven, 2021). Third, our sample was female dominated and further studies should address the gender differences.…”
Section: Limitations and Future Researchmentioning
confidence: 88%
“…Specially, the investigation focused on the mechanisms that inform the stressor–strain relationship in the context of remote work during the pandemic. In doing so, we respond to a recent call to examine the specific ways in which work stressors impact individual outcomes during the COVID-19 pandemic (van Zoonen & Ter Hoeven, 2021 ). Specifically, in response to the overarching research question presented in this study, the findings indicate that challenge stressors and hindrance stressors demonstrate a similar negative impact on adjustment to remote work, whereas hindrance stressors are more strongly negatively related to social support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Event system theory states that the stronger the event (the more novel, disruptive, and critical), the more attention and resources it attracts from individuals, which in turn has a greater impact on their behavior [ 39 , 40 ]. The COVID-19 pandemic is characterized by all three of these features.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%